Two new species of Pleurothallis (Orchidaceae: Pleurothallidinae) allied to P. cardiothallis, with a note on flower activity - Pupulin, Franco (2017)
Two new species of Pleurothallis subsection Macrophyllae-Fasciculatae from Costa Rica, allied to P. cardiothallis, are described and illustrated, and their relationships discussed. Pleurothallis scotinantha is compared with P. oncoglossa, from which it can be easily distinguished by the concolorous, dark purple flowers, the distinctly de exed petals, and the lip without a distal callus that is not hooked at the apex. Pleurothallis navisepala, from the northern Costa Rican cordilleras, is compared with P. cardiothallis, from which it is distinguished by the simultaneous owering of two or more owers, the much smaller size of the flowers, and the deeply navicular sysnsepal, which prevents complete spreading of the ower. A key to the Costa Rican species of the group is presented. Observations on oral behavior in the species allied to P. cardiothallis are provided and the possible function of this behavior is discussed. The visit of a tephritid y to the flowers of P. navisepala is described.